The Role of Matrix Metalloproteinase in Human Body Pathologies 2017
DOI: 10.5772/intechopen.71662
|View full text |Cite
|
Sign up to set email alerts
|

Heart Remodelation: Role of MMPs

Abstract: Myocardium is comprised of a number of cell types. Although most plentiful by volume, cardiac myocytes are greatly outnumbered by nonmyocyte cells, the latter constituting approximately 70% of all myocardial cells, of which approximately 90% are cardiac fibroblasts (CFBs). To maintain the integrity of the cardiac extracellular matrix (ECM) is one of the primary functions of cardiac fibroblasts. ECM represents a network structure that provides the structural and functional integrity to the heart. Besides that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…In addition, fibroblasts surround cardiomyocytes, and the myocyte function depends on the fibroblast. In pathological processes, cytokines and growth factors alter the fibroblast phenotype by increasing the secretion of ECM proteins that lead to fibrosis [ 25 , 26 , 27 ]. Fibroblasts and myofibroblasts are the central MMP-secreting cells in the heart and are indicated as a therapeutic target for the treatment of myocardial infarction, hypertension and HF [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fibroblasts surround cardiomyocytes, and the myocyte function depends on the fibroblast. In pathological processes, cytokines and growth factors alter the fibroblast phenotype by increasing the secretion of ECM proteins that lead to fibrosis [ 25 , 26 , 27 ]. Fibroblasts and myofibroblasts are the central MMP-secreting cells in the heart and are indicated as a therapeutic target for the treatment of myocardial infarction, hypertension and HF [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the numerous MMPs characterized and identified, gelatinases (MMP-2 and MMP-9) play a role in remodeling of the cardiac infrastructure. They have been reported to play a role in inflammation-induced imbalance of extracellular matrix turnover in the heart ( Pytliak et al, 2017 ). It has been demonstrated that non-toxic cadmium stimulates MMP-9 and MMP-2 expression in the cardiovascular system inducing vascular inflammation and promoting atherosclerosis ( Knoflach et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The diversified evolution of cardiac damage mediated by ROS further emerges through the demonstration that their concentration can also variously modulate the action of the different isoforms of MMP-2. Particularly, it has been proved that, in the setting of an acute redox injury, a considerable part of newly synthesized MMP-2 is activated, thus remaining within the cell associated with the sarcomeric proteins and determining the cleavage of several crucial components of the contractile apparatus [ 11 , 45 ]. On the other hand, under persistent oxidative stress and the subsequent activation of an alternative intronic promoter, the expression of the NT-MMP-2 isoform occurs, promoting the following: the induction of specific mitochondrial-nuclear stress signaling, the impairment of cardiomyocyte function, and finally ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%